Chapter 3: Demographic challenges of Europe in the new millennium: Swedish family policies as an answer to them? (Edward Elgar Publishing, 2021)
Post-industrialisation brought new social risks connected to changing labour markets and the individualisation of families. These and emerging demographic challenges paralleled by changing gender roles require new strategies of welfare states to handle. Sweden has long pursued a social investment strategy and aligned its family policies to promote commodification, de-familialisation, de-gendering of employment and care, and social and gender equality. The resulting high female labour force participation rates, high share of fathers' care engagement, and comparatively high fertility indicate that Sweden has met the new challenges quite successfully. This chapter delineates the challenges faced by Europe's welfare states and the core features of the Swedish family policies as a way to tackle new social risks.